P270 Mesenchymal stromal cells contribute to the recovery of secondary loss of response to infliximab in patients with ulcerative colitis. (27th May 2021) - Knyazev, O; Kagramanova, A V; Lishchinskaya, A; Li, I; Shkurko, T; Kulakov, D; Babayan, A; Zvyaglova, M; Zhulina, E; Parfenov, A
Abstract: Background: Long-term experience with infliximab (IFХ) shows that within a year, 20–30% of patients with ulcerative colitis (UC) develop acquired drug resistance (secondary inefficiency). Aim: To establish the possibility of overcoming the secondary inefficiency of IFX in UC patients using mesenchymal stromal cells (MSC). Methods: In the IBD treatment Department, the clinical status of 84 UC patients receiving IFX therapy was evaluated. Secondary loss of response was registered in 28 UC patients, which required optimization of IFX therapy. 12 patients (group 1), in order to overcome the secondary loss of response, were administered MSCS three times every 4 weeks, 16 patients with UC (group 2) received standard optimized IFX therapy. The effectiveness of therapy was evaluated after 12 weeks of therapy (reduction of the Mayo score) and normalization of laboratory parameters (ESR, C-reactive protein (CRP), hemoglobin, fecal calprotectin (FCP). The comparative analysis was carried out using the method of four-field tables using nonparametric statistical criteria. Results: In 10 (83.3%) of 12 patients of group 1, a significant positive dynamics was observed after 12 weeks: a decrease in the Mayo index and normalization of laboratory parameters (ESR, CRP, hemoglobin, FCP). In 4 (25.0%) patients with UC from group 2, against the background of optimized IFX therapy, a significant positive dynamics was also observed with a decrease in the meio index and an improvement in ESR, CRP, hemoglobin and FCP levels. However, 12 patients from group 2 were transferred to therapy with other anti-TNF-α drugs and drugs with a different mechanism of action (RR-0.222, 95% CI 0.061–0.812; x 2 - 7.146; p=0.00334). Conclusion: The use of mesenchymal stromal cells of the bone marrow helps to overcome the secondary loss of response to infliximab in patients with ulcerative colitis.